Majority Group Members' Negative Reactions to Future Demographic Shifts Depend on the Perceived Legitimacy of Their Status: Findings from the United States and Portugal - Outten, H. Robert; Lee, Timothy; Costa-Lopes, Rui; Schmitt, Michael T.; Vala, Jorge (Frontiers in Psychology, 2018)
Using concepts from social identity theory (Tajfel & Turner, 1979), we examined whether racial/ethnic majority group members’ reactions to future demographic shifts is a function of the degree to which they perceive their ingroup’s higher status in society to be legitimate. In two studies, participants who varied in the degree to which they perceived their group’s status to be legitimate were either exposed to real projections for 2060 (i.e., large decline in proportion of population that is the “majority” group), or fake projections for 2060—that resembled current figures (i.e., small decline). In Study 1, White Americans who perceived their status to be highly legitimate expressed greater intergroup threat, and negative feelings (anger and fear) toward minorities after exposure to projections with a large decline in the relative size of the White American population. In contrast, demographic shift condition had no effect on intergroup threat and negative feelings toward minorities among White Americans who perceived their status to be relatively illegitimate; negative feelings and threat remained low across both conditions. Similarly, in Study 2, ethnic Portuguese people in Portugal exposed to projections in which their was a large decline in the relative size of the ethnic Portuguese population experienced more intergroup threat and expressed a greater desire to engage in anti-immigration behaviors. The effect of demographic shift condition on intergroup threat and anti-immigration behaviors was stronger among ethnic Portuguese who perceived their status to be legitimate compared to ethnic Portuguese people who perceived their status to be relatively illegitimate. These results highlight that across different cultural contexts, majority group members’ beliefs about the legitimacy of intergroup relations can affect their reactions to the prospect of increased diversity.